2005
DOI: 10.1111/j.1365-2141.2005.05848.x
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and dexamethasone followed by thalidomide and dexamethasone is an effective well tolerated initial therapy for multiple myeloma

Abstract: SummaryAmong the drug combinations designed for the initial treatment of multiple myeloma, none has been unequivocally shown to be superior. However, a regimen leading to a high response rate and a low incidence of adverse events is highly desirable. We report the results of a phase II clinical trial involving 45 patients with Durie-Salmon stage II and III multiple myeloma. Doxorubicin and dexamethasone were given for 2 or 3 months followed by thalidomide and dexamethasone for 2 months (AD-TD regimen) with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Third, although the serum FLC assay is a very reliable test, it is important to closely monitor laboratory variation. 16 Strict guidelines are required with regard to usage times for the serum FLC assay kits. It should also be noted that serum FLC assay testing might be useful in the prognostic and response evaluation of patients who also have a measurable serum and/or urine M-component in the future, given its recently reported prognostic value in M-gammopathy of undetermined significance (MGUS).…”
Section: Response Categoriesmentioning
confidence: 99%
“…Third, although the serum FLC assay is a very reliable test, it is important to closely monitor laboratory variation. 16 Strict guidelines are required with regard to usage times for the serum FLC assay kits. It should also be noted that serum FLC assay testing might be useful in the prognostic and response evaluation of patients who also have a measurable serum and/or urine M-component in the future, given its recently reported prognostic value in M-gammopathy of undetermined significance (MGUS).…”
Section: Response Categoriesmentioning
confidence: 99%
“…17 However, this combination administered to patients who are not candidates for autotransplantation led to results similar to those achieved with conventional chemotherapy. 8 Better results can be obtained when chemotherapeutic agents are added to or administered before 18 the thalidomide-dexamethasone combination. [10][11][12][13] At present, it remains unclear which single or other chemotherapy regimen is the best one to be combined with thalidomidedexamethasone to achieve a higher CR rate associated with an acceptable toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…There is one published study in which patients were treated with doxorubicin and dexamethasone for 2 or 3 months followed by thalidomide and dexamethasone for 2 months. 42 The authors found that normalization of the rFLC after one or two cycles of treatment, which occurred in 8 of 37 patients, was significantly associated with the achievement of CR or nCR (Po0.003). The significance of this finding is uncertain because no information about PFS or OS as related to rFLC normalization is provided.…”
Section: International Myeloma Working Group Guidelinesmentioning
confidence: 99%